2012
DOI: 10.4103/0970-9185.92452
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in the incidence of shivering with perioperative dexmedetomidine: A randomized prospective study

Abstract: Background and Aims:Shivering is distressing to the patient and discomforting to the attending anesthesiologist, with a varying degree of success. Various drugs and regimens have been employed to abolish the occurrence of shivering. The present study aims to explore the effectiveness of dexmedetomidine in suppressing the postanesthetic shivering in patients undergoing general anesthesia.Materials and Methods:The present study was carried out on 80 patients, in American Society of Anesthesiologists I and II, ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
99
1
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(115 citation statements)
references
References 31 publications
14
99
1
1
Order By: Relevance
“…The rapid speed of infusion also determines, to a large extent, the higher incidence of side-effects such as bradycardia, apnoea and irregular ventilation. 37 The results of our study are consistent with the study of Shehabiet al 23 claimed that dexmedetomidine produced predictable falls in BP and heart rate in patients given dexmedetomidine sedation in the ICU. Their results showed 16% reduction in mean systolic blood pressure (SBP) and 21% reduction in heart rate.…”
Section: Discussionsupporting
confidence: 82%
“…The rapid speed of infusion also determines, to a large extent, the higher incidence of side-effects such as bradycardia, apnoea and irregular ventilation. 37 The results of our study are consistent with the study of Shehabiet al 23 claimed that dexmedetomidine produced predictable falls in BP and heart rate in patients given dexmedetomidine sedation in the ICU. Their results showed 16% reduction in mean systolic blood pressure (SBP) and 21% reduction in heart rate.…”
Section: Discussionsupporting
confidence: 82%
“…[15][16][17] The mechanism of action by which dexmedetomidine inhibits shivering is complex. Several studies have demonstrated that dexmedetomidine alleviated shivering mainly through its central α2-adrenoreceptor agonist effect.…”
Section: Discussionmentioning
confidence: 99%
“…3,9,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] Other control agents included fentanyl, [33][34][35][36] remifentanyl, 37,38 meperidine, 15 midazolam, [39][40][41] propofol, 43,44 ketamine, 45,46 tramadol, 24,47 clonidine, 42 propacetamol, 48 and buprenorphine 49 ( 8 were reported in the 39 included trials, and all studies reported every endpoint mentioned in the Methods section (reporting bias). 8 however, some bias 8 may exist in of the two trials, 27,32 as the length of surgery was not clear.…”
Section: Study Characteristicmentioning
confidence: 99%